Table of Content - - (Journal of Educational and Psychological Sciences, 2024)
Table of Content: 1. The impact of using mobile learning on academic achievement and the development of expressive reading skills in the English language course for secondary school students in the city of Jeddah Mr. Abdullah Yahya Albaeth 2. The classroom management issues faced by early childhood teachers Ms. Sharefah Saad Algamdi 3. The reality of using virtual laboratory in Madrasati platform for Chemistry subject teachers in secondary schools in Riyadh Mr. Abdallah Saltan Al-Baqami, Dr. Turki Saad Al-Zahrani 4. The role of Employing e-learning in integrating students with learning difficulties with ordinary students from the point of view of basic stage teachers in South Hebron Directorate Dr. Feryal Abdulaziz Amro, Mrs. Maryam Rafieq Al-Hamouri 5. Psychometric Characteristics of Sustainable Behaviour Metric for Middle School Students Ms. Fatima Abdullah Al-Shahrani, Co-Prof. Nawal Gram Allah Al-Ghamdi 6. Psychological Stress among Mothers of Autistic Children in light of Counseling Services provided to them in Al-Madinah Ms. Waad Abdul-Karim Al-Mutairi 7. Job compatibility among kindergarten principals in the State of Kuwait from the teachers’ point of view Dr. Amna Haidar Al-Hearz